Fructose separation from sorghum syrup by using HPLC approach: a review - Nur Istianah; N.A. Kartina; Dego Yusa Ali (International Journal of Advance Tropical Food, 2020)
Liquid sugar available today is usually the result of dissolving granulated sugar using hot water. Sorghum syrup can be obtained from the concentrate without involving crystallization, centrifugation, sieving and drying and dissolving processes. However, the sorghum syrup produced from the concentrate still containing complex sugar components such as sucrose, sugar, fructose and others. This review was examined the separation of fructose from sorghum syrup using the HPLC approach. Compared with artificial sweeteners or sugar derivative products such as dextrose, maltodextrin, sorbitol, saccharin, sucralose, and xylitol, sorghum syrup still has lower economic value. The manufacture of these sugar derivatives generally uses chemical processes such as chlorination of sucralose, hydrogenation of xylitol or enzymatic processes and fermentation of fructose. Chemical processes in general can pose a danger to consumer health, while enzymatic and biological processes require high operational costs and complex processes of enzyme and cell separation such corn fructose production. Chromatography is a technology for separating complex mixtures such as sorghum concentrates to obtain separate components, such as fructose syrup and byproducts. On a laboratory scale, sugar fractionation or fructose purification is generally carried out using High Performance Liquid Chromatography (HPLC) with the Carbopac ion exchange column as the stationary phase and ultrapure water as the mobile phase. The industrial scale fractionation in the food sector is still applied to palm oil processing. This is a great opportunity to conduct research related to the components of sorghum concentrates using chromatography column fractionation technology to obtain pure fructose with greater process efficiency and economics.